ECONOMIC ABUSE AND ITS IMPACT ON WOMEN'S MENTAL HEALTH IN TIRUVALLUR DISTRICT - Victoria, A. Lilly; B. Venugopal; Kumar, K.V.D.Kishore (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The mental health of women is greatly impacted by economic abuse, which is a kind of domestic violence that is less obvious but extremely devastating. This is especially true in rural and semi-urban areas, such as the Tiruvallur district in Tamil Nadu. In this study, the incidence of economic abuse on women in this region, as well as its patterns and the psychological impact it has on them, are investigated. Through the use of a mixed-methods approach that includes surveys and in-depth interviews with 120 women, the research finds typical abusive behaviors. These behaviors include financial control, exploitation, sabotage of work possibilities, and coerced economic reliance. The results of the study indicate that there is a significant connection between the experiences of women who have been subjected to economic abuse and heightened levels of melancholy, anxiety, low self-esteem, and feelings of despair among those women. Specifically addressing this component of gender-based violence, which is frequently disregarded, the study underscores the urgent need for focused treatments in the field of mental health, programs that empower individuals economically, and governmental reforms. For women who have survived economic abuse in Tiruvallur and other comparable socio-cultural situations, having a better understanding of the confluence of economic abuse and mental health can lead to the development of more comprehensive support networks.